2012
DOI: 10.3354/meps09885
|View full text |Cite
|
Sign up to set email alerts
|

Impact of climate change on coastal versus estuarine nursery areas: cellular and whole-animal indicators in juvenile seabass Dicentrarchus labrax

Abstract: The effects of thermal conditions of coastal and estuarine nurseries, both in the present and in the near future, on juvenile fish were compared. The response of the European seabass Dicentrarchus labrax was investigated through a long-term experiment in captivity, where 0-group juveniles were exposed to temperatures that reflect the average summer temperature that they encounter in coastal (18°C) and estuarine nurseries (24°C), and also the temperature that they endure inside estuaries during heat waves (28°C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
20
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 26 publications
(32 reference statements)
0
20
0
Order By: Relevance
“…These experimental temperatures had previously been used with other temperate and subtropical fishes with minimal effects on survival (Vinagre et al . ,b,c). Based on their distribution ranges and the habitats where they live, our initial expectation was that seabreams would be among the more heat‐resistant species at temperate latitudes.…”
Section: Methodsmentioning
confidence: 99%
“…These experimental temperatures had previously been used with other temperate and subtropical fishes with minimal effects on survival (Vinagre et al . ,b,c). Based on their distribution ranges and the habitats where they live, our initial expectation was that seabreams would be among the more heat‐resistant species at temperate latitudes.…”
Section: Methodsmentioning
confidence: 99%
“…Induced oxidative stress is also described as responsible for an increase in cholinesterase activity in neuronal models (Melo et al 2003), and an increase in synaptic neurotransmission caused by increased cell membrane fluidity is also related with swimming disturbances in goldfish (C. auratus) exposed to heat stress (Szabo et al 2008). Recent findings indicate an increase in the combined expression of two heat shock proteins (Hsc/Hsp 70) in muscle of juvenile seabass exposed to 24 and 28°C (Vinagre et al 2012b), pointing out that molecular processes of reparation are occurring at these temperatures and also corroborating the hypothesis of induced thermal stress responses at 24°C or higher in seabass juveniles.…”
Section: Effects Of Temperature On Fish Health Statusmentioning
confidence: 99%
“…It is also an economical important species being used for human consumption, and that may be adversely affected by temperature increase (Cabral and Costa 2001;Vinagre et al 2009), particularly considering the areas that are in the southern range of their distribution and in the upper limit of their thermal tolerance. Given its pertinence, this species has been selected in recent studies focusing on this subject, including on thermal tolerance definition (Madeira et al 2012), and on the effects of climate change and heat waves on mortality, growth, condition (Vinagre et al 2012c), oxidative stress parameters (Vinagre et al 2012a) and heat shock protein expression (Vinagre et al 2012b). However, at the best of our knowledge, the physiological parameters selected for the present study were not previously tested in D. labrax exposed to different temperatures, except two of the antioxidant parameters, LPO levels and CAT activity (Vinagre et al 2012a).…”
Section: Introductionmentioning
confidence: 99%
“…(), as lipid peroxidation increased when seabass were maintained outside the optimal temperature interval. Thermal stress was suggested as a possible cause, further confirmed by the high variation of specific cellular expressions such as heat stress proteins (HSP70; Vinagre, Madeira, Narciso, Cabral, & Diniz, ). Another low‐temperature adaptation of seabass was reported by Trigari et al.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results were described by Vinagre et al (2012a), as lipid peroxidation increased when seabass were maintained outside the optimal temperature interval. Thermal stress was suggested as a possible cause, further confirmed by the high variation of specific cellular expressions such as heat stress proteins (HSP70; Vinagre, Madeira, Narciso, Cabral, & Diniz, 2012b). Another low-temperature adaptation of seabass was reported by Trigari et al (1992), where they showed a lipid metabolism modulation, triggered by changes in the deposition of fatty acids, particularly in liver cell membranes.…”
Section: Biomarkersmentioning
confidence: 91%